Роль макрофагов в развитии болевого синдрома при аденомиозе - Славчева, О. С.; Бондаренко, С. А.; Сулаева, О. Н.; Сулаєва, Оксана Миколаївна; Slavcheva, O. S.; Bondarenko, S. A.; Sulaieva, O. N. (My University, 2015)
Для оценки участия макрофагов в развитии болевого синдрома при аденомиозе проведено пилотное изучение распределения в стенке матки нервных волокон и макрофагов, выявленных иммуногистохимически с использованием моноклональных антител к белкам нейрофиламентов и CD68. Показано наличие зональной гетерогенности количества и морфологических характеристик нервных волокон в миометрии при аденомиозе.Максимальное количество нервных волокон было выявлено вокруг крупных артерий сосудистого слоя миометрия и в периваскулярных зонах участков ремоделирования миометрия на фоне их лейкоцитарной инфильтрации.Оценка CD68+клеток выявила большое количество макрофагов в периваскулярном компартменте и вокруг конусов роста эктопических желез эндометрия. Таким образом, развитие болевого синдрома при аденомиозе ассоциировано с увеличением количества нервных волокон и макрофагов в периваскулярном регионе и зонах ремоделирования миометрия. З метою оцінки участі макрофагів у розвитку больового синдрому при аденоміозі проведено пілотне вивчення розподілу у стінці матки нервових волокон і макрофагів, виявлених імуногістохімічно з використанням моноклональних антитіл до білків нейрофиламентов і CD68. Показано наявність зональної гетерогенності кількості та морфологічних характеристик нервових волокон в міометрії за умов аденоміозу. Максимальна кількість нервових волокон була зафіксована навколо великих артерій судинного шару міометрію та в периваскулярних зонах ділянок ремоделювання міометрію на тлі їх лейкоцитарної інфільтрації. Оцінка CD68+клітин виявила переважну локалізацію макрофагів у периваскулярному компартменте і навколо конусів росту ектопічного ендометрію. Таким чином, розвиток больового синдрому при аденоміозі асоційований зі збільшенням кількості нервових волокон і макрофагів в периваскулярному регіоні та зонах ремоделювання біометрію. According to the modern concept of neuro-immune interactions, one of the potential causes of enhanced angiogenesis, the growth of the nerves and pain and may be hyperactivation of macrophages Immunohistochemical evaluation showed the presence of a diffuse network of macrophages in the endometrium and myometrium of patients with adenomyosis. During morphometric analysis revealed heterogeneity of distribution of macrophages in the different functional areas Perivascular localization of CD68 positive cells was predominant. In addition, a large number of macrophages identified in regions of the leukocyte infiltration of stroma especially around the outbreaks adenomyosis with signs of dystrophy and desquamation cells. A small number of single macrophages were Located diffusely between bundles of smooth muscle cells in the stroma of the myometrium. Conclusion. The data indicate that one of the key links of adenomyosis pain pathogenesis is immunopathologi cal process, accompanied by increase in the number of macrophages in the wall of the uterus that leads to stimulation of angiogenesis and nerves growth. Perspectives of future investigation. To sum up, in the future the elucidation the molecular mechanisms of activation of macrophages in endometriosis will develop an optimal strategy for the prevention of disease progression and the development of pain. Number of nerve fibres in the wall of the uterus in patients with adenomyosis were detected around the large arteries of the vascular layer of the myometrium and in the spaces between it.
Роль макрофагів у розвитку больового синдрому при аденоміозі
Role of Macrophages in Pain Syndrome Development at Adenomyosis
Keywords: аденомиоз; нервные волокна; ангиогенез; макрофаги; аденоміоз; нервові волокна; ангиогенез; макрофаги; adenomyosis; nerve fibres; angiogenesis; macrophages